Early Childhood Development in Sub-Saharan Africa : Policy and Programs - Colletta, Nat J. (World Bank, Washington, DC, 2012)
This study, review of early childhood development policy and programs in Sub-Saharan Africa, is the second in a series of three studies conducted under the World Bank's Africa regional early child development (ECD) initiative. The first described the condition of young children in Africa and pointed to the benefits of ECD in increased efficiency of primary and secondary school investments, children's enhanced economic contribution to society, and the reduction of social inequity. The third study will synthesize lessons drawn from the preceding two studies and from case studies in Kenya, South Africa, and Mauritius. The findings of this review are that weakened family and public social sector support for child development create a tremendous need for complementary and alternative forms of child care, and that there are models. The review selects eleven case studies from across the Sub-Saharan region to illustrate a range of possibilities for an integrated response to the physical, socio-emotional, cognitive, economic and cultural dimensions of young children's development, so that impact is maximized through the interconnectedness of investments.